Validity of STEM-based modelling instrument for pre-service teachers of mathematics education - Hidayat, Riyan (South East Asia Association for Institutional Research, 2024)
Mathematical modelling involves a set of interconnected skills that allow students to translate real-world situations into mathematical representations and vice versa. This research aimed to develop the instrument consisting of sub-competency; simplifying, mathematising, computing, interpreting and validating. The study utilized a cross sectional survey research design. A total of 135 pre-service teachers of mathematics voluntarily selected using convenience sampling methods, participated in this study. The data was analysed by item-CVI (I-CVI), S-CVI and exploratory factor analysis (EFA). This tool's preliminary versions demonstrated good content validity for both the individual items and overall, for STEM-based material (S-CVI/UA = 0.88; S-CVI/Ave = 0.93). The Kappa value was K = 0.88, indicating an excellent value of validity. The development of STEM-Based modelling instrument revealed great item-content validity and scale-validity for assessing sub competency in pre-service teachers. At the same time, EFA revealed that STEM-based modelling instrument had five sub-components; simplifying, mathematising, computing, interpreting and validating. The results showed that the STEM-based modelling instrument’s reliability was good. Creating and verifying the STEM-focused modelling tool designed for preservice teachers is essential in mathematics education and research. It offers a valuable means to evaluate and improve the essential skillset related to mathematical modelling, benefiting educators and STEM students alike. Moreover, the research's approach and discoveries have the potential to influence forthcoming investigations and educational methodologies across diverse fields.